PENGARUH PARTISIPASI ANGGARAN DAN MOTIVASI KERJA TERHADAP KINERJA MANAJERIAL PADA PERANGKAT DAERAH DI KABUPATEN MALUKU TENGGARA - Fitria Fitria; Christina Sososutiksno; Kevin Hermanto Tupamahu; Jefry Gasperz; Salomi Jacomina Hehanusa (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to examine the effect of budget participation and motivation on managerial performance in The Local Bureaucracy in Southeast Maluku Regency. This study uses a quantitative approach. The population in this study were three people from each The Local Bureaucracy within the Southeast Maluku Regency Government. The sample was determined using the census method and obtained 123 respondents. The research results show (1) budget participation has a positive and significant effect on managerial performance in The Local Bureaucracy in Southeast Maluku Regency; and (2) motivation has a positive and significant effect on managerial performance in The Local Bureaucracy in Southeast Maluku Regency.